Global Climate Change: Security Problems of Climate Refugees - Neslihan Arslan (Sosyal Siyaset Konferansları Dergisi)
Throughout history, people have migrated from one place to other regions or countries for various reasons. Migrations occur in line with one’s wants in some cases, while in other cases the individual migrates out of necessity. Climate refugees are one of the rising concepts in the migration literature in recent years and have also found their place in studies as a different type of migration. Global climate change can be a determinant in people’s preference for an alternative region due to the difficulties they experience in one area, such as lack of a safe water supply, access to natural resources, or shelter. Although climate refugees refer to people who have to relocate due to the negative effects of climatic conditions, refugees are seen as the focus of many legal, economic, political, and cultural problems in terms of the countries where they end up. This study has a theoretical basis and discusses the concepts of global climate change and climate refugees. The study evaluates the problems of security refugees face in terms of climate-related issues, legal status, and social life. In addition, the study includes within its scope the perspective of states and international legislation toward climate refugees.